Histone Deacetylase 6 and the Disease Mechanisms of α-Synucleinopathies - Lemos, Miguel; Stefanova, Nadia (Frontiers in Synaptic Neuroscience, 2020)
The abnormal accumulation of α-Synuclein is a prominent pathological feature in a group of diseases called α-Synucleinopathies, such as Parkinson´s disease, dementia with Lewy bodies and multiple system atrophy. The formation of Lewy bodies and glial cytoplasmic inclusions in neurons and oligodendrocytes, respectively, is highly investigated. However, the molecular mechanisms behind α-Synuclein improper folding and aggregation remain unclear. Histone deacetylase 6 (HDAC6) is a class II deacetylase, containing two active catalytic domains and an ubiquitin-binding domain. The properties of HDAC6 and its exclusive cytoplasmic localization allow HDAC6 to modulate the microtubule dynamics, acting as a specific α-tubulin deacetylase. In addition, HDAC6 is able to bind ubiquitinated proteins, facilitating the formation of the aggresome, a cellular defense mechanism to cope with higher levels of misfolded proteins. Several studies report that the aggresome shares similarities in size and composition with Lewy bodies and glial cytoplasmic inclusions. In fact, HDAC6 is found to co-localize with α-Synuclein in neurons and in oligodendrocytes, together with other aggresome-related proteins. The involvement of HDAC6 in several neurodegenerative diseases is already under discussion, however the results obtained by modulating HDAC6 activity are not entirely conclusive. The main goal of this review is to summarize and critically discuss previous in vitro and in vivo data regarding the specific role of HDAC6 in the context of α-Synuclein accumulation and protein aggregation in α-Synucleinopathies.